Molecular phylogeny and morphology reveal four new species of Thelephora (Thelephorales, Basidiomycota) from subtropical China, closely related to T. ganbajun - Yang, Shi-Rong; Wei, Yu-Lian; Yuan, Hai-Sheng (Frontiers in Microbiology, 2023)
The genus of Thelephora is a group of cosmopolitan ectomycorrhizal fungi with basidiocarps of morphological diversity which has an extremely scarce species reported from forest ecosystem in China. In this study, phylogenetic analyses of Thelephora species from subtropical China were carried out based on multiple loci including the internal transcribed spacer (ITS) regions, the large subunit of nuclear ribosomal RNA gene (nLSU) and the small subunit of mitochondrial rRNA gene (mtSSU). Maximum Likelihood and Bayesian analyses were used to construct the phylogenetic tree. The phylogenetic positions of four new species, Th. aquila, Th. glaucoflora, Th. nebula and Th. pseudoganbajun, were revealed based on morphological and molecular evidence. Molecular analyses demonstrated that the four new species were closely related to Th. ganbajun and formed a clade with robust support in the phylogenetic tree. In morphology, they share some common morphological characteristics, including flabelliform to imbricate pilei, generative hyphae more or less covered by crystals and subglobose to irregularly lobed basidiospores (5–8 × 4–7 μm) with tuberculate ornamentation. These new species are described and illustrated, and compared to similar morphological or phylogenetically related species. A key to the new and allied species from China is provided.